KINERJA TERMINAL BELLO KUPANG BERDASARKAN KONDISI LALU LINTAS PADA TERMINAL BAYANGAN PEREMPATAN JALUR 40 SIKUMANA-BELLO - Frans, John H.; Utomo, Sudiyo; Nubatonis, Marisa N. (Jurnal Teknik Sipil, 2017)
Review performance needs to be done because during the last several years, the terminal is not work well,so that people have difficulty to get any transportation for their activities. This research was conducted to find out the feasibility of terminal according the terminal clasification that is Type C,physical performance based on the traffic condition in terminal bayangan, the satisfaction of the customer and the strategy to be implementedto make the terminal work properly.From the result of the feasibility analysis can be concluded that Terminal Bello is quite feasibility to be classified as type C terminal with score equal to 58,93%.The result of physicalperformance analyzes was unsatiesfied yet since from the whole aspect only the location and waiting time that meet the criteria, whereasthe performance considered unsatisfactory which has been evaluated from the road user perception werethe public transportation service and sanitation, from the driver perception were road condition, passengers, information system, parking area, garrage and the regulation of passengers allocation by route. The interview’s result by SWOT quadrant matrix show that Terminal Bello belongs to IV quadrant which means that the terminal is poor to face any big challenge ahead so that the proper strategy needed isminimize weaknesses to avoid threats better